Global Food Security and Ukraine’s Contribution to Its Provision - PARKHOMENKO, V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The aim of the article is to study the essence of global food security and assess Ukraine’s contribution to its provision. The essence of the concept of “global food security” is clarified. The tasks of specialized institutions dealing with the problem of global food security are described. Ukraine’s participation in the FAO and the UN World Food Security Committee has been clarified. It has been established that the Global Food Security Index (GFSI) is used to assess food security around the world, which includes four components: food affordability, food affordability, food quality, safety an d security, natural resources and sustainability. Ukraine’s contribution to the world food market has been studied. The structure of the total merchandise exports of Ukraine was analyzed, it was found that the share of agri-food products is 40.6%, and the share of plant products is 22.8%. Ukraine’s place in world food exports is specifi ed, the geographical structure of food exports is considered. Ukraine’s contribution to food security in Africa and Asia is analyzed. The dynamics of Ukrainian grain exports to the world market has been studied. The risks and threats to global food security related to the Russian armed invasion of Ukraine are described. The USDA forecast for grain exports from Ukraine is given. The conclusion is made about the need to protect and support the production of agricultural products in Ukraine under martial law.